Developing an evaluation framework of public participation for urban planners in Malaysia - Bello, Ashiru (2014)
The increasing interest in public participation can be viewed either as a failure of democracy or a complement to democracy. Inadequacy of policies relating to public participation has been identified as one of the explanations for the failure of projects and programmes relating to public participation. Pattern of professional practice (professionals being at the fore-front in designing specific operational policies) is seldom documented. The rapid transitional nature of Malaysia’s development in which several development projects (such as the different components of the new nation’s capital project as well as those of the Iskandar conurbation cluster and the Klang river restoration project) requiring comprehensive planning input are springing up, makes it an ideal case for examining planners’ pattern of public participation evaluation and integrating it to the design of future projects. This study therefore aims at developing an evaluation framework of public participation for urban planners in Malaysia. Adapting the Laurian and Shaw approach (in studying the American planners’ professional practice), the pattern of public participation evaluation is examined among Malaysian planners with the help of Malaysian Institute of Planners (MIP). Components of evaluation such as its focus and motivation, projects’ characteristics as well as the engagement techniques are subsequently weighed numerically to form the basis for developing the P-SOP framework for linking planners’ evaluation experiences to subsequent operational policies. This entails the scripting of defined combination syntax in PHP to be run from a locally hosted web server. The source of the script is then exported (from the client’s HTML view) to a spread sheet environment through a flexible procedure that will guide subsequent operational policies in the design of participatory processes. It has been found that, planners in Malaysia do not perceive the role of the public in planning process to be mere information exchange, nor are they comfortable with the highest rungs of full project control. Although the planners were of the view that focus group discussion is the most influential method in promoting success of participatory process, the participatory processes utilizing workshops as an engagement technique, were found to produce more successful results. The P-SOP framework that will be developed will serve as a flexible guide for subsequent design of participatory processes particularly in the choice of engagement techniques to be utilised in a particular project.